Assessment Manual: Practical Tool for Keeping Assessment Processes on Track - Leslie L. Griffin (Academic Chairpersons Conference Proceedings, 2016)
Department chairs are tasked with ensuring that complex and comprehensive assessment plans related to academic programs are in place and monitored, providing outcomes data that drive program improvement. Participants will review a model Assessment Manual designed to keep stakeholders on track within the assessment system.
Keywords: assessment outcomes TaskStream data accountability